2016
DOI: 10.1186/s12913-016-1873-9
|View full text |Cite
|
Sign up to set email alerts
|

Total joint arthroplasty: practice variation of physiotherapy across the continuum of care in Alberta

Abstract: BackgroundComprehensive and timely rehabilitation for total joint arthroplasty (TJA) is needed to maximize recovery from this elective surgical procedure for hip and knee arthritis. Administrative data do not capture the variation of treatment for rehabilitation across the continuum of care for TJA, so we conducted a survey for physiotherapists to report practice for TJA across the continuum of care. The primary objective was to describe the reported practice of physiotherapy for TJA across the continuum of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Furthermore, as this was a survey of physiotherapists, these data may reflect how physiotherapists expect to treat patients rather than the realities of what patients are referred for or receive. In other healthcare systems, Jones et al [25] has previously explored practice variations in physiotherapy following THR and TKR, although only within one region of Canada (Alberta). They reported some variability across providers, but this was largely on an individual level rather than at a region level, as assessed in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as this was a survey of physiotherapists, these data may reflect how physiotherapists expect to treat patients rather than the realities of what patients are referred for or receive. In other healthcare systems, Jones et al [25] has previously explored practice variations in physiotherapy following THR and TKR, although only within one region of Canada (Alberta). They reported some variability across providers, but this was largely on an individual level rather than at a region level, as assessed in our data.…”
Section: Discussionmentioning
confidence: 99%
“…As no validated tool existed for benchmarking management following TJA, a survey was designed using both open-and closed-ended questions. Questions were informed by previous surveys completed documenting physiotherapy management of individuals following TJA (Jones et al, 2016;Naylor et al, 2006). The survey questions were reviewed and piloted by a group of senior physiotherapists and researchers.…”
Section: Methodsmentioning
confidence: 99%
“…The Royal Australasian College of Surgeons (2018) suggested clinical variation following TJA may be a sign of system inefficiencies and therefore opportunity for improvement. Physiotherapy plays an essential role in the perioperative care of patients undergoing TJAs; however, variations in practice have been described in the acute and sub-acute settings (Artz et al, 2013;Jones et al, 2016). In a cohort of privately funded patients in Australia, patient-related factors explained only 24.6% of the variance in inpatient rehabilitation rates post-TKA with surgeon-or hospitalrelated factors comprising the remaining 75.4% (Schilling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation before and after TJA is an important healthcare topic for QI development 25 . The high volume and growing demand for TJA procedures 11e13, 15,16,26 , significant costs to healthcare systems 18,27,28 , high quality evidence to support the effectiveness of rehabilitation on pre-and post-operative patient outcomes 19,20,22e24 and patient satisfaction 29 , together with marked variations in rehabilitation practices 30,31 and outcomes 32,33 , warrant the effort to develop QIs and address care gaps. Furthermore, based on our previous research and clinical experience, we identified a number of opportunities to change clinical practice behaviours and improve quality of care and patient experiences 29 .…”
Section: Introductionmentioning
confidence: 99%